Cathelicidins: Opportunities and Challenges in Skin Therapeutics and Clinical Translation - Lenka Dzurová; Edita Holásková; Hana Pospíšilová; Gabriela Schneider Rauber; Jitka Frébortová (Antibiotics)
Cathelicidins are a group of cationic, amphipathic peptides that play a vital role in the innate immune response of many vertebrates, including humans. Produced by immune and epithelial cells, they serve as natural defenses against a wide range of pathogens, including bacteria, viruses, and fungi. In humans, the cathelicidin LL-37 is essential for wound healing, maintaining skin barrier integrity, and combating infections. Cathelicidins of different origins have shown potential in treating various skin conditions, including melanoma, acne, and diabetic foot ulcers. Despite their promising therapeutic potential, cathelicidins face significant challenges in clinical application. Many peptide-based therapies have failed in clinical trials due to unclear efficacy and safety concerns. Additionally, the emergence of bacterial resistance, which contradicts initial claims of non-resistance, further complicates their development. To successfully translate cathelicidins into effective clinical treatments, therefore, several obstacles must be addressed, including a better understanding of their mechanisms of action, sustainable large-scale production, optimized formulations for drug delivery and stability, and strategies to overcome microbial resistance. This review examines the current knowledge of cathelicidins and their therapeutic applications and discusses the challenges that hinder their clinical use and must be overcome to fully exploit their potential in medicine.